Economic burden of disease and mortality of intracranial haemorrhage under oral FXai: a German claims data analysis - Huttner, Hagen B.; Scherg, Felix; Kopke, Katarina; Schultze, Michael; Kossack, Nils; Gerner, Stefan T.; Kuramatsu, Joji; Schwab, Stefan (Neurological Research and Practice, 2025)
Background: Intracranial haemorrhage (ICH) is one of the most serious complications of anticoagulant therapy with oral factor Xa inhibitors (FXai). To meet an urgent medical need of optimising treatment pathways, we assessed the frequency of ICH during oral FXai treatment, as well as the associated burden on the German healthcare system. Methods: Our study was based on a claims database comprising over 4 million people with statutory health insurance in Germany. The study included people initiating oral FXai treatment for the first time between 2016 and 2021, and who experienced ICH during a three-year treatment period. For a balanced comparison of hospitalisations, costs, and mortality, propensity score matching between patients with and without ICH was performed. Results: During the study period, 78,086 patients had started oral FXai therapy, of which 530 experienced ICH during the therapy. The incidence rate of ICH was highest within the first 90 days after the start of oral FXai therapy during follow-up with 0.64 events per 100 patient-years (PY; 95% CI: 0.52–0.77%). Three-month mortality rates were significantly higher among patients who had experienced an ICH event (39.4%; 95% CI: 35.4–43.8%), as opposed to patients without ICH (5.9%; 95% CI: 4.2–8.3%). This difference prevailed during follow-up, while mortality increased at roughly equal rates in both patient groups. Patients with ICH were on average hospitalised for 40.4 days/PY (95% CI: 35.7 days – 45.2 days) in the first year after the event; comparable patients without ICH were hospitalised for 10.8 days/PY (95% CI: 8.3 days – 13.2 days). Annual total costs per patient were €37,328 (95% CI: €32,243–€42,412) for patients with ICH, and €10,564 (95% CI: €9,298–€11,831) for patients without ICH. Hospitalisation costs were the main driver with 86.1% versus 50.8%, respectively. Conclusions: Incidence rates of ICH during oral FXai therapy were within the range of other published real-world data. Duration of hospitalisations, associated costs, and mortality were high and significantly higher for patients with ICH than for comparable patients without ICH. The high burden on the healthcare system highlights the need for preventive measures and more efficient treatment pathways for patients with ICH under oral FXai therapy.
CRIS-Team Scopus Importer:2025-04-11
Keywords: Anticoagulation; Direct oral anticoagulant; DOAC; ICH; Intracranial haemorrhage; Oral factor Xa inhibitor; Oral FXai